Is the "sustainable retail business model" a pipedream? A multiple case study of nordic retailers - Charlotte Walker; Harri Hokkanen (Journal of Business Models (JOBM), 2024)
Purpose: Increasing public awareness of social and environmental problems has led to critique of firms, rais- ing questions about their efforts in addressing sustainability. Due to their unique position in the supply chain, retailers have enormous potential to influence sustainable progress through their business models. However, many global retailers have fallen into various sustainability-related scandals. Therefore, the purpose of this study is to identify activities that retailers are undertaking to address sustainability. Design/Methodology/Approach: Recent reports indicate that Nordic retailers have established themselves as sustainability pioneers. Consequently, this exploratory research is based on an empirical multiple case study, fo- cusing on eight retailers from Denmark, Finland, Norway, and Sweden. This study draws from sustainability re- ports and employs directed content analysis to identify retailers' activities. Findings: The study identified 44 retailing activities used to address sustainability and revealed that only six (out of 45) sustainable business model design patterns are commonly used by pioneer retailers. The findings illustrate both the common and emerging patterns in retail, and further highlight the areas that are lacking in retail business model design. Originality/Value: By exploring how a megatrend is addressed by commercial actors, this research connects retail business model and sustainable business model literature, proposes a new role for retailers as change agents, and suggests five propositions that can guide traditional retailers on their sustainability journeys.
Keywords: 650; Sustainability; Retail Business Model; Sustainable Business Model; Retailers' Activities; Pioneers; Nordic